Iatrogenic Aortic Pseudoaneurysm: a Forgotten Complication - Almeida, S (2014)
Pseudoaneurysms of the ascending aorta are a rare complication of cardiac surgery. However, the poor prognosis associated with this condition if untreated makes early diagnosis and treatment important. We present the case of a 66-year-old woman who had undergone mitral valvuloplasty 12 days previously, who was admitted with a diagnosis of new-onset atrial fibrillation. The transthoracic echocardiogram showed a clot in the right atrium and anticoagulation was initiated, followed by antibiotic therapy. After further investigation, the patient was diagnosed with a pseudoaneurysm of the ascending aorta and underwent surgical repair, followed by six weeks of antibiotic therapy. She was readmitted six months later for an abscess of the lower sternum and mediastinum. After a conservative approach with antibiotics and local drainage failed, recurrence of a large pseudoaneurysm compressing the superior vena cava was documented. A third operation was performed to debride the infected tissue and to place an aortic allograft. There were no postoperative complications.